Effect of Inclusion of Silk Worm Pupae Meal in the Diet with or without Enzyme Supplementation on Nutrient Utilization and Growth Performance in Crossbred Pigs - Medhi, D.; Bhuyan, R.; Ahmed, H.F.; Saikia, B.N. (Indian Journal of Animal Nutrition, 2018)
Thirty six weaned crossbred (Hampshire Ã— Assam local) pigs of uniform body weight of 14.51Â±0.14 kg were allotted to six dietary treatments, in a 3 Ã— 2 factorial arrangement and offered ad lib. quantity of iso-nitrogenous (CP-18% during grower) and iso-caloric (ME-3170 kcal/kg comprising of three levels of silk worm pupae meal incorporation replacing fish meal at 0, 50 and 100% with or without â€œAnizymeâ€ supplementation at the rate of 65 g/100 kg feed. The experiment was conducted for a period of 70 days. No significant differences were observed for average daily gain, dry matter intake, digestibility of nutrients as well as balance of energy and nitrogen among different experimental groups except that the digestibility of ether extracts increased by supplementation of Anizyme in the ration. It was concluded that crossbred growing pigs can be reared on concentrate ration with silk worm pupae meal as a sole animal protein source replacing fish meal at 100% level (7% of the ration) with supplementation of Anizyme without any adverse effect.